Admission Strategy for International New Students at the University of Mataram - Menshuliang; Sudirman; Heri Hadi Saputra (International Journal of Scientific Multidisciplinary Research, 2024)
Recruiting international students is highly beneficial yet challenging for universities in Indonesia. This study raised research focusing on strategies applied by Indonesian Universities to attract international students' willingness to enroll. It also figured out the challenges and solutions encountered by the students in their initial studies. This study adopted Vincent Tinto's theory about the factors affecting students' academic accomplishments and learning failures. Qualitative design, case study approach, and open-ended questionnaires were implemented. This study invited three staff members of the International Affairs and International Center as the participants. Thematic analysis was adopted utilizing Atlas. Ti software to analyze the data from the respondents following Kawulich's (2004) framework, encompassing Narrative, Coding, Interpretation, Confirmation, and Presentation. The result demonstrated some strategies implemented by Mataram University for international students, such as providing proper facilities, including library and study spaces, access to technology, and a health center. The university also utilizes international alumni to endorse the university in their home country. Alongside the hurdles, the university provides students with a welcoming ceremony that includes a language course, academic orientation, and cultural adaptation programs upon their arrival